Simile in Demon Thief Novel by Darren Shan - Khairani Sinaga; Lutfiansyah Lutfiansyah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Literature has many forms, not only painting, but also writing. Each literature has its own uniqueness and one of the things that is unique is the writing in the novel. Novel is a writing in the form of a book that has various styles of writing in it. These writing styles are called figurative language. Figurative language also has many forms, one of which is simile. Simile is a figure of speech that illustrates or compares something in an explicit, or uncomplicated way. This study examines how many similes are contained in a literary work and explains them. By using descriptive qualitative method, all types of similes, namely (as, like, as...as, as if, and as though) will be discussed in detail. By studying this simile, it is hoped that it will make the readers of the novel better understand and better understand the stylistic message conveyed by the author to the reader.